(untitled) (Journal of the Bangladesh Agricultural University, 2020)
Replacement of fish meal with soybean meal is an effective way to relieve the pressure on fish meal as the supply of this feed ingredient is dwindling and certainly is not sustainable in long term at present levels in commercial feeds. This study was conducted to assess the growth performance (length, weight, specific growth rate) of Nile tilapia (Oreochromis niloticus) by replacing the percentage of fish meal with soybean meal in formulated diets. Nile tilapia (O. niloticus) fry were collected from Bangladesh Fisheries Research Institute, Mymensingh and treated with five formulated diets D1, D2, D3, D4, D5 respectively containing 0%, 25%, 50%, 75% and 100% soybean meal as a replacement of fish meal. Forty O. niloticus having an initial weight of 6.60±0.13 g and initial length of 5.42±0.17 cm were fed these diets twice a day for 6 months. For growth analysis, length and weight of the fish were recorded at 30 days interval for 6 months. Significantly higher (P<0.001) body weight was observed in D1 (SBM 0) and D2 (SBM 25) groups at 90, 120, 150 and 180 days; and in D3 (SBM 50) and D4 (SBM 75) groups at 150 and 180 days compared to D5 (SBM 100) group. Significantly higher (P<0.05) body length was observed in D1 (SBM 0) and D2 (SBM 25) groups at 180 days compared to D5 (SBM 100) group These results suggest that the replacement of FM up to 75% with SBM showed better growth performance in Nile tilapia (O. niloticus). J Bangladesh Agril Univ 18(1): 152–156, 2020 https://doi.org/10.5455/JBAU.94754